OPTIMASI CAMPURAN PATI JAGUNG DAN AVICEL PH 101 SEBAGAI BAHAN PENGHANCUR PADA TABLET EKSTRAK BUAH PARE (Momordica charantia L.) SECARA GRANULASI BASAH - Dwi Saryanti; Heny Ismawati; Iwan Setiawan (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2019)
Bitter melon fruit (Momordica charantia L.) can be used as traditionally to reduce blood sugar levels. Avicel PH 101 and corn starch are efficacious as fillers, disintegration excipient and binders. The combination of Avicel PH 101 with corn starch is expected to be able accelerate the tablet disintegration time of tablet. This research was aimed to get the optimum formula tablets of bitter melon extract tablets using combination of corn starch and avicel PH 101. Bitter melon extract was formulated in tablet with wet granulation method. Bitter melon extract was obtained by maceration with ethanol 70% as solvent. Tablet formula based on the Simplex Lattice Desaign method uses Design Expert software version 11 with parameters that are used weight uniformity, hardness, friability and disintegration time. The results obtained from the simplex lattice design compared with the results of testing using the SPSS 18 program using the One Sample T-Test with a confidence level of 95%. The result of this research indicate bitter melon extract was made by tablets with wet granulation method with a combination of Avicel PH 101and corn starch, a formula with a ratio of 51% : 49% selected as the optimum formula with weight uniformity, hardness, friability and disintegration time meeting the requirements. Keywords : bitter melon extract, tablets, corn starch, avicel PH 101, simplex lattice design